ANALSIS DINAMIK MODEL PREDATOR-PREY DENGAN PEMANENAN LINEAR PADA KEDUA POPULASI - M. Adib Jauhari Dwi Putra; Erik Maurten Firdaus; Findasari Findasari (JURNAL ILMU KOMPUTER DAN MATEMATIKA, 2023)
We studied the Lotka Volterra predator-prey model with linear harvesting of prey and predators. We found that there are 3 equilibrium points, namely the point of extinction of the two species, the point of extinction of predators and the point of coexistence of both species, predator and prey. The stability and existence of the three points depend on the parameter values in the model. We found that the populations of both species were sustainable if the growth rate of the predators was greater than the mortality and yield rates of the predators. Overharvesting led to the extinction of both species. We also perform numerical simulations using the Python programming language to see the system behavior graphically